Patiotemporal evolution patterns and driving factors of agricultural ecological efficiency in the Yangtze River Economic Belt, China - Liu, Xieqihua; Zhu, Yi; Zhang, Bo; Lu, Hanqing; Zhang, Tao (Frontiers in Sustainable Food Systems, 2025)
Promoting the improvement of agricultural ecological efficiency (AEE) under the “dual carbon” goals is an important way to drive the high-quality development of the Yangtze River Economic Belt (YEB). This study, based on panel data from 11 provinces and cities along the YEB from 2008 to 2023, first accounts for agricultural carbon sources and sinks, then incorporates them into a non-desired output super-efficiency SBM model to measure the AEE of the YEB, and finally uses the Tobit model to analyze the factors influencing AEE. The study found that (1) the net agricultural carbon sink of the YEB increased from 108.160 million tons in 2008 to 142.890 million tons in 2023, and the net agricultural carbon sinks of Anhui, Jiangsu, and Sichuan ranked among the top three in the basin. (2) The AEE of the YEB gradually increases from 0.625 in 2008 to 1.024 in 2023, and the AEE accelerates after 2020; In 2008, most provinces and cities were primarily located in areas characterized by low surplus and low efficiency, but by 2023, they had predominantly transitioned to areas with high surplus and high efficiency, along with some remaining in low-surplus, high-efficiency zones. In terms of the type of AEE, in 2008, provinces and municipalities were mainly concentrated in low-surplus low-efficiency zones, low-surplus low-efficiency zones, and high-surplus low-efficiency zones, while in 2023, provinces and municipalities were primarily focused in high-surplus high-efficiency zones and low-surplus high-efficiency zones. (3) In terms of influencing factors, the living standard of farmers, the level of financial support for agriculture, and the level of agricultural marketization will promote the improvement of AEE, while the level of farmland water conservancy facilities, the rate of disaster, and the level of urbanization will hinder the improvement of AEE. Therefore, this paper proposes optimizing the structure of agricultural production factors, implementing differentiated low-carbon agricultural development strategies, and strengthening governmental collaborative governance. This study aims to offer a fresh viewpoint on how to better assess AEE, provide a Chinese approach to achieving agricultural carbon neutrality in global river basins, and suggest practical steps to reach the “Carbon Peak and Carbon Neutrality” goal in the YEB.